FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN AYAM PEDAGING UD PAK NARNO PONOROGO - Audry Putri Maharani; Wijianto; Dwi Warni Wahyuningsih (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of service quality, product quality, and price on customer satisfaction at the broiler chicken MSME (UD Pak Narno) in Ponorogo Regency. Customer satisfaction is a key focus in an increasingly competitive business environment, especially in the food industry that demands optimal quality and service. A quantitative approach was employed, using survey methods through questionnaires distributed to 97 respondents who are active customers of UD Pak Narno. Accidental sampling was the method of sampling that was employed. Multiple linear regression was used to analyze the data in order to look at the independent variables' simultaneous and partial effects on customer satisfaction. The results indicate that, partially, service quality and price significantly influence customer satisfaction, while product quality does not show a significant effect. Simultaneously, all three independent variables have a significant impact on customer satisfaction. These findings offer valuable insights for UD Pak Narno's management to focus more on improving service quality and implementing competitive pricing strategies to enhance customer loyalty. Keywords: Service Quality, Product Quality, Price, Customer Satisfaction, MSMEs